Thermal, structural and mechanical properties of melt drawn cur-loaded poly(lactic acid) fibers - Syed Shaharuddin, Sharifah Imihezri; Qairol, A.A.B.; Hassan, Noor Azlina; Muhammad Khairusalleh, Nor Khairusshima (Elsevier BV, 2017)
Turmeric has been one of the most treasured spices and is well known for having health promoting properties. In this study, PLA fibers were loaded with curcumin at 1, 3 and 5 wt% and were successfully drawn via an in-house built fiber drawing tower. The structure of the fibers was characterized using Fourier transform infrared (FTIR) spectroscopy. The thermal analysis using differential scanning calorimetry (DSC) showed almost similar Tg and Tm of the neat PLA and cur-loaded fibers. The average diameter of the fibers obtained were in the range of 300-200 μm. In comparison to neat PLA fiber, it was observed that the strength and modulus decreased by 35% and 37% respectively as curcumin was added at 5 wt%. It was also noted that the surface of the cur-loaded PLA fibers featured randomly distributed 'beads of string' feature.